A fourteen-tubes based semi-analytical model for fluidelastic instability threshold prediction of tube bundles in two-phase cross flow. (August 2021) - Cheng, Jianhua; Jing, Jianping; Wang, Yuerong; Gao, Tianrun; Cong, Jiqing
Highlights: A semi-analytical model with a new layout of 14 flexible tubes is presented. Three sets of experimental data are used for modeling verification. Accuracy and efficiency of models with 1, 7, and 14 tubes are compared. Interactions between tubes and cross-flow are analyzed in the time and spatial domain. Parametric study about three empirical inputs of the models is carried out. Abstract: The semi-analytical model (a.k.a. the tube-in-channel model) needs less empirical inputs and considers interactions between tube movements and cross-flow variables, and is well used in fluidelastic instability (FEI) threshold prediction of tube bundles. However, despite numerous flexible tubes in engineering practice, tube-in-channel models with more than 7 tubes are not yet studied. In this paper, a new tube-in-channel model with a layout of 14 flexible tubes, rather than the reported 1, 5, or 7 tube(s), is established and used for FEI threshold prediction of rotated triangular tube bundles in two-phase cross-flow. Five sets of experimental data are used for verifying this model, of which the accuracy and efficiency are compared with those of tube-in-channel models with 1 and 7 tube(s). Influences of the attachment angle, the separation angle, and the time-delay parameter on performances of these three models are also investigated. Since its numerical predictions agree well with the experiments, the present 14-tubes model shows potential applications in steam generator design.